Induction and Maturation of Hepatocyte-Like Cells In Vitro: Focus on Technological Advances and Challenges - Xie, Ye; Yao, Jia; Jin, Weilin; Ren, Longfei; Li, Xun (Frontiers in Cell and Developmental Biology, 2021)
Limited by the poor proliferation and restricted sources of adult hepatocytes, there is an urgent need to find substitutes for proliferation and cultivation of mature hepatocytes in vitro for use in disease treatment, drug approval, and toxicity testing. Hepatocyte-like cells (HLCs), which originate from undifferentiated stem cells or modified adult cells, are considered good candidates because of their advantages in terms of cell source and in vitro expansion ability. However, the majority of induced HLCs are in an immature state, and their degree of differentiation is heterogeneous, diminishing their usability in basic research and limiting their clinical application. Therefore, various methods have been developed to promote the maturation of HLCs, including chemical approaches, alteration of cell culture systems, and genetic manipulation, to meet the needs of in vivo transplantation and in vitro model establishment. This review proposes different cell types for the induction of HLCs, and provide a comprehensive overview of various techniques to promote the generation and maturation of HLCs in vitro.